Clays and Clay Minerals, Vol. 58, No. 3, 340–350, 2010. - Sommer, Alicia E.; Fetter, Geolar; Bosch, Pedro; Lara, Victor H (The Clay Minerals Society, 2010)
The morphology of hydrotalcites determines their use in catalysis, biomedicine, or adsorption as they may work as anion exchangers or as drug deliverers. In catalysis, reagents need access to as much surface area as possible; in biomedicine, drugs have to be encapsulated. However, the parameters and the mechanisms which direct the synthesis towards a certain morphology are not well understood. Precipitating agents or crystallization conditions are expected to play a crucial role. In the present study, hydrotalcites were synthesized in the presence of two precipitating agents (NaOH or NH4OH) under three different crystallization conditions (conventional, microwave, or ultrasound irradiation) which determined the morphology of the final product, layered or vesicular. The features are explained through the template effect of the liberated gases on the co-precipitation and crystallization processes and consequently on the final structure/morphology of the synthesized solids. Indeed, the nodular particles crystallize using the effluent gases as templates. Fractal dimension and particle-size distributions, determined by small-angle X-ray scattering (SAXS) and gas adsorption are compared and correlated to the presence of ammonium. Although the materials obtained are heterogeneous, it is possible to propose a microscopic geode model.
New Template Effect In Hydrotalcite Synthesis. Nodular Vs. Layered Morphologies
gsccm58305-som.pdf -- 912KB
Keywords: Periodicals; Geology; Ammonium Hydroxide; Globular; Hydrotalcite; Microwave Irradiation; Nanoporosity; Nodule; Spherical Materials; Ultrasound Irradiation; Vesicle